2019
DOI: 10.1126/sciadv.aax5095
|View full text |Cite
|
Sign up to set email alerts
|

Ordered colloidal clusters constructed by nanocrystals with valence for efficient CO 2 photoreduction

Abstract: The ability to construct discrete colloidal clusters (CCs) as complex as molecular clusters is limited due to the lack of available colloidal building blocks and specific directional bonds. Here, we explore a strategy to organize anisotropic Prussian blue analog nanocrystals (NCs) toward CCs with open and highly ordered structures, experimentally realizing colloidal analogs to zeolitic clathrate structures. The directional interactions are derived from either crystallographic or morphological anisotropy of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 68 publications
1
54
1
Order By: Relevance
“…Most recently, frame‐like structures also exhibit similar advantageous features for photocatalytic reactions. [ 24 ] Moreover, frame‐like structures can also enhance the mass‐transfer processes during photocatalytic reactions. Therefore, combining the merits of hollow structures and frame‐like structures may lead to high photocatalytic performance.…”
Section: Figurementioning
confidence: 99%
“…Most recently, frame‐like structures also exhibit similar advantageous features for photocatalytic reactions. [ 24 ] Moreover, frame‐like structures can also enhance the mass‐transfer processes during photocatalytic reactions. Therefore, combining the merits of hollow structures and frame‐like structures may lead to high photocatalytic performance.…”
Section: Figurementioning
confidence: 99%
“…The activity loss in the prolonged period is mainly ascribed to the photofading effect of the ruthenium photosensitizer, in agreement with previous observations. [5,6,[12][13][14][15] The total products generation of CoP-600 and CoP after photoreaction for 4 h is about 134 and 107 μmol ( Figure S7), giving the catalytic turnover numbers (TONs) of 12 and 9.7 based on the corresponding cocatalysts, which reveals the catalysis essence of the CO 2 reduction reaction.…”
mentioning
confidence: 99%
“…[25] Lou et al developed a series of Co-contained oxides for enhanced photochemical CO 2 reduction. [26][27][28] Recently, Co single atom catalysts have been demonstrated high activity towards photocatalysis and electrochemical syngas production. [29][30][31] Through reviewing the published works, we found that the research on amorphous Co-based compounds remains deficient.…”
mentioning
confidence: 99%